Joyful Learning Metdhod: A Teacher's Effort In Developing Critical Thinking Skills - Siti Rezeki, Jeni; Muslimah; Lutfi, Saiful (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
The purpose of this study was to determine the application of the joyful learning method. This type of research uses descriptive qualitative methods with the subject of 32 students. Data collection techniques are observation, interviews and documentation, and data validation techniques use source tringulation while data analysis includes data collection, data reduction, data display, and conclusion drawing. The results of this study improve critical thinking skills with the application of joyful learning methods, because from planning the teacher has implemented the learning process well as the teacher has applied, namely 1. Preparing the classroom atmosphere 2. Motivating students to take part in learning 3. Delivering learning objectives, As for the learning implementation stage the teacher applies. The joyful learning method emphasizes the use of approaches that make the learning process more interesting, interactive, and fun for students. With games and discussions in learning, teachers can encourage students to think critically, collaborate, and gain a deeper understanding of the subject matter.